Wind desalination and power: an affordable and renewable solution to address water shortages - Julian David Hunt; Andreas Nascimento; Amaro Olímipio Pereira Junior; Paulo Sergio Franco Barbosa; Walter Leal Filho; Yoshihide Wada (International Journal of Sustainable Energy)
There has been a steep increase in investment in more affordable approaches to desalinated seawater using renewable energy sources. This paper proposes desalinating seawater with a pump and a motor-generator installed inside wind turbine nacelles, to desalinate seawater with reverse osmosis membranes without electricity. The technology was named Wind Desalination and Power (WDP), as the wind turbine can pump seawater and generate electricity. This study presents a comprehensive analysis and rationale behind the design, estimates its economic viability, and assesses the global potential of the proposed technology. Results demonstrate that the cost for seawater desalination with WDP is 0.64 USD/m3, which is 20% cheaper than conventional wind desalination. The paper shows that WDP has the potential to enhance water resilience in arid regions while at the same time contributing to grid stability and renewable energy integration.